The Influence of Search, Solve, Create and Share (SSCS) Learning Model Based on Physical Simple Tools to the Ability of Critical Thinking - Viatri Areskiana Aziz; Mujasam Mujasam; Sri Rosepda Br Sebayang (Kasuari: Physics Education Journal (KPEJ), 2021)
This experimental study aims to determine the effect of Search, Solve, Create and Share (SSCS) models based on simple teaching aids on students' critical thinking skills before and after learning. This research was conducted at YPK Oikumene Manokwari Senior High School in the 2019/2020. The research method used was a Quasi Experimental Design study with the type of Control Group Pretest Posttest Design. The research subjects were class XI IPA 1 with 15 students as the experimental class using the SSCS models and class XI IPA 2 with 17 students as the control class using conventional learning models. The research instrument used in the form of tests is essaystest. The research data used paired samples t-test with a significance value α = 0.05. Decision making is based on sig 2 tailed calculations of 0.00. Sig value 2 tailed 0.00 <α = 0.05 so that the hypothesis decision is H0 rejected or Ha accepted. This means that there is an influence of the SSCS models on students' critical thinking skills. The ability profile of students can be seen from the average value in working on critical thinking questions that is the overall average value of 65.71 included in the medium criteria, while in the control class the overall average value of 42.31 is included in the very low criteria. The value obtained means that the SSCS model based on simple teaching aids influences students' critical thinking skills.